Bhopal: Anatomy of a Crisisby ShrivastavaPaul. Cambridge, MA: Ballinger, 1987, 184 pp., $19.95, cloth. - Jermier, John M. (Academy of Management Review, 1988)
The article presents a review of the book “Bhopal: Anatomy of a Crisis,” by Paul Srivastava.